KEKERASAN SIMBOLIK DALAM NOVEL LUKA PEREMPUAN ASAP KARYA NAFI’AH AL-MA’RAB: PERSPEKTIF SOSIOLOGI SASTRA - Suci Puspita Sari; Sugiarti Sugiarti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2022)
Symbolic violence is violence that occurs subtly and unconsciously, so that there is no resistance from the party being dominated. The objectives of this study were (1) to describe the form of symbolic violence and (2) to describe the factors of symbolic violence in the novel Luka Perempuan Asap by Nafi'ah Al-Ma'rab in the perspective of sociological literature. This study uses a sociological literary approach that focuses on symbolic violence according to Pierre Bourdieu. The source of research data is the novel Luka Perempuan Asap by Nafi'ah Al-Ma'rab. The research data is in the form of story sequences such as narratives, sentences, and paragraphs that represent symbolic violence. The results showed that (1) forms of symbolic violence were characterized by euphemization and censorship mechanisms. The forms of euphemization mechanisms include obligation, efficiency, image, bonus giving, trust, and kindness. Meanwhile, the forms of sensory mechanism are in the form of marginalization, coercion, threats, and disappointments. (2) The factors causing symbolic violence in the novel Luka Perempuan Asap by Nafi'ah Al-Ma'rab are due to economic capital in the form of money, cultural capital in the form of achievement, while symbolic capital is in the form of titles and social status.